Malignant mesotheliomas with unknown exposure to asbestos: a re-examination - Mensi, Carolina; Poltronieri, Anna; Romano, Alessandro; Dallari, Barbara; Riboldi, Luciano; Bertazzi, Pier Alberto; Consonni, Dario (La Medicina del Lavoro, 2016)
Introduction: Malignant Mesothelioma (MM) is a rare neoplasm associated with asbestos exposure. In 24,5% of MM cases reported to the Lombardy Mesothelioma Registry (LMR), asbestos exposure has been defined as “unknown”. Objective: To evaluate the cases with “unknown exposure to asbestos” diagnosed in 2000-2004 in agreement with new knowledge about source of asbestos exposure. Methods: Information regarding exposure has been reviewed in order to select the cases susceptible of further investigations, including: interview of relatives and/or colleagues; further evaluations by local PSAL (Prevention and Security in workplace) services; contact of industrial hygienists; analysis of production processes. The same procedure has been followed for extra-occupational exposure. These cases have been subjected to the LMR evaluation group. Results: Fourthy four out of 364 (12,1%) MM have been reclassified. In 47,7% of the cases, a “possible occupational exposure” has been recognized, 15,9% have been attributed a “certain occupational exposure”, while 36,4% an extra-occupational (domestic, environmental and leisure-time) exposure. No significant differences between age, sex, cancer site, diagnostic certainty, residence, year of diagnosis, interviewed subjects were detected. The occupational sector with the highest amount of reclassifications was the clothing production. Conclusions: The detailed reconstruction of clinical and occupational history and of lifestyle habits of patients affected by MM, close cooperation with Local Services of Occupational Medicine and literature review make it possible for previously overlooked asbestos exposure to be acknowledged.